Failure modes and non-destructive testing techniques for fiber-reinforced polymer composites - Muhammad Muzammil Azad; Jaehyun Jung; Muhammad Umar Elahi; Muhammad Sohail; Prashant Kumar; Heung Soo Kim (Journal of Materials Research and Technology)
Prognostics and health management (PHM) is an enabling technology essential for the safe operation and conditional maintenance of any engineering system. Over the past two decades, the use of fiber-reinforced polymer (FRP) composites has increased to develop high-strength, lightweight, and durable composite structures. PHM technology has been widely adopted in the composites industry to address challenges such as damage detection, localization, remaining useful life (RUL) prediction, and maintenance scheduling. However, implementing PHM technologies for FRPs necessitates a thorough understanding of their failure modes and the non-destructive testing (NDT) techniques commonly used to assess their health condition. Therefore, this review provides a comprehensive discussion on the failure modes of FRP composites based on practical loading conditions, examines several NDT techniques employed on FRP composites, detailing their advantages and limitations, and highlights the current challenges while providing future directions for the use of NDT techniques in PHM of composite structures. Thus, the review aids practitioners, the scientific community, and new researchers in understanding the failure modes of FRP composites and exploring recent advancements in NDT techniques to address the current challenges and limitations in PHM of composite structures.